The Potential Role of GJA1 and SPP1 Expressed by the Endometrium Based on Single Cell Transcriptome Analysis in Endometrial Infertility - Zhenzhen Lu; Qianqian Tang; Chunyan Chen; Xiaojie Zhao; Ying Gao; Qiongqiong Wei (Clinical and Experimental Obstetrics & Gynecology)
Background: Endometrial infertility accounts for a significant proportion of infertility cases, and single-cell transcriptome data have revealed that hub genes may play an important role during pregnancy. Methods: Based on the endometrial single-cell sequencing data from National Center for Biotechnology Information (NCBI) database, we performed clustering, staging, and functional analyses to screen and validate key genes affecting endometrial infertility. Results: Through bioinformatics analysis, we found that the proportion of ciliated cells peaked from the early to mid secretory phase, ciliary motility decreased in the mid secretory phase, while the hub gene that connexin 43 (GJA1) and secreted phosphoprotein 1 (SPP1) expressed in the endometrium may determine successful pregnancy. In immunohistochemistry validation, GJA1 and SPP1 were significantly highly expressed in the endometrium of a normal pregnancy, compared to recurrent miscarriage. Similarly, GJA1 and SPP1 were expressed higher in the fetal villus of a normal pregnancy as compared to recurrent miscarriage, while no difference was found in the decidua. CellPhoneDB and protein–protein interactions (PPIs) indicated an interaction among notch receptor 1 (NOTCH1), GJA1 and SPP1. Conclusions: GJA1 and SPP1 exhibit higher expression levels in the endometrium and fetal villus of a normal pregnancy as compared to recurrent miscarriage, suggesting that GJA1 and SPP1 may play a pivotal role in endometrial infertility.